Motor behavior. Connecting mind and body optimal performance - Ives, J. C. (Wolters Kluwer Health, 2014)
This book takes a functional approach to motor control and learning that is in keeping with the modern use and understanding of these topics. It takes the basic concepts of motor learning and motor control and integrates them to discuss questions such as how our emotions affect physiological outcome. This title is unique in that it goes beyond just explaining motor control and motor learning to help students understand how these disciplines interact with each other to affect behavior. Chapter 1. Introduction to Motor Behavior and the Mind-Body ConnectionUNIT I: Motor Control Chapter 2. Neural Mechanisms in Planning and Initiating Movement Chapter 3. Peripheral Neuromuscular Mechanisms in Executing Movement Chapter 4. Peripheral Sensory Systems in Monitoring Movement Chapter 5. Movement Models UNIT 2. Motor Learning Chapter 6. Understanding Motor Skill and Motor Abilities Chapter 7. Learning and the Development of Expertise Chapter 8. Information Processing and Motor Skill Performance Chapter 9. Practice and Instruction UNIT 3. Mind, Body, and Brain Chapter 10: Muscle Tone and Postural Control Chapter 11. Orthopedic Injury, Rehabilitation, and Prehabilitation Chapter 12. Strength, Power, Speed, and Agility